2013
DOI: 10.1093/cvr/cvt219
|View full text |Cite
|
Sign up to set email alerts
|

Physical training and hypertension have opposite effects on endothelial brain-derived neurotrophic factor expression

Abstract: Cardiovascular BDNF is mainly localized within endothelial cells in which its expression is dependent on endothelial function. These results open new perspectives on the role of endothelial BDNF in cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 44 publications
2
80
0
Order By: Relevance
“…Authors suggested new perspectives on the role of endothelial BDNF in cardiovascular health. 22 Our conclusions suffer from the small size of our study group (n ¼ 31). The presented P values were not corrected for multiple comparisons and we could not perform reliable multivariate analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Authors suggested new perspectives on the role of endothelial BDNF in cardiovascular health. 22 Our conclusions suffer from the small size of our study group (n ¼ 31). The presented P values were not corrected for multiple comparisons and we could not perform reliable multivariate analysis.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that the level of plasma BDNF decreased in the aged 16 and patients with CAD. 17 Consistently, decreased BDNF expression in vascular endothelium was associated with hypertension, 18 a common complication of CAD. Reduced TrkB expression in tissues was also found during aging.…”
Section: Discussionmentioning
confidence: 84%
“…Corresponding sedentary rats were kept in their housing cage that was placed at the proximity of the treadmill apparatus. We previously showed that such a modality of physical training (treadmill activity with a horizontal position, 30 minutes/day, 18 m/minute, for 7 consecutive days) induced a mild increase in citrate synthase activity in skeleton muscles, did not change blood pressure in WKY rats and SHR, 13 and resulted in a twofold increase in mature BDNF levels in the cortex when induced in control Wistar rats. 14 …”
Section: Physical Trainingmentioning
confidence: 99%